The Corporate Tax Haven Index: A new geography of profit shifting - Leyla Ates; Alex Cobham; Moran Harari; Petr Janský; Markus Meinzer; Lucas Millan-Narotzky; Miroslav Palanský (Charles University in Prague, Institute of Economic Studies (IES), 2020)
The geography of corporate profit shifting is often presented in public discourse in simplistic and inaccurate terms. Not only can this easily mislead audiences, but it shapes political responses to the problem in such a way as to undermine the prospects for genuine progress. In this paper, we set out a new approach to the geography of profit shifting, based on a range of objectively verifiable criteria. These are combined in the Corporate Tax Haven Index, published for the first time in 2019. We present the technical argument for the index as a meaningful representation of the global distribution of the risks of corporate tax abuse and explore the new geography that emerges. The key findings show the UK's dominant responsibility for corporate tax avoidance risks and the colonial roots of many exploitative double tax treaties. We end by considering the index's political implications for the immediate process of international tax reform, and for the longer-term prospects for global governance in this area. We conclude that greater clarity about the geography of profit shifting is likely to support growing demands for redistribution not only of taxing rights but also of decision-making power in the global architecture for tax governance.
Keywords: F36; F63; F65; H26; O16; 330; Corporate tax; multinational corporations; tax; transparency; tax avoidance; tax havens; profit shifting